PENDAMPINGAN PENGEMBANGAN PRODUK DAN PEMASARAN KEPADA MASYARAKAT PERKEBUNAN JAMBU KRISTAL KM 24 BALIKPAPAN - Amalia, Dwi Nur (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
The crystal guava plantation located at KM 24 Gang Perjuangan II, Karang Joang Village is one of the areas being developed by Aneka Tani Balikpapan. The problems that arise in crystal guava plantations are the lack of a marketing strategy and there is still no innovation of processed products in the crystal guava. The purpose of this community service activity is to provide education and practice to the crystal guava plantation community to understand digital marketing and processed products that can be produced from their agricultural products. The methods of activities carried out for our community service activities are conducting observations and interviews, presentations and questions and answers, practice, giving modules, and the evaluation stage. The results that will be obtained from our community service program are the socialization of the manufacture of processed guava products as evidenced by the feedback from the audience, the practice of making processed guava crystals, the socialization of digital marketing as evidenced by the feedback from the audience, and the implementation of digital marketing of crystal guava plantations by creating an Instagram account and Facebook.